A study on the wake-up effect of ferroelectric Hf0.5Zr0.5O2 films by pulse-switching measurement. Issue 3 (29th October 2015) - Kim, Han Joon; Park, Min Hyuk; Kim, Yu Jin; Lee, Young Hwan; Moon, Taehwan; Kim, Keum Do; Hyun, Seung Dam; Hwang, Cheol Seong
Abstract : The wake-up effect from the ferroelectric Hf0.5 Zr0.5 O2 film and the influence of field cycling on the interfacial layer were examined by the pulse-switching experiment. Abstract : The appearance of ferroelectric (FE) and anti-ferroelectric (AFE) properties in HfO2 -based thin films is highly intriguing in terms of both the scientific context and practical application in various electronic and energy-related devices. Interestingly, these materials showed a "wake-up effect", which refers to the increase in remanent polarization with increasing electric field cycling number before the occurrence of the fatigue effect. In this work, the wake-up effect from Hf0.5 Zr0.5 O2 was carefully examined by the pulse-switching experiment. In the pristine state, the Hf0.5 Zr0.5 O2 film mostly showed FE-like behavior with a small contribution from AFE-like distortion, which could be ascribed to the involvement of the AFE phase. The field cycling of only 100 cycles almost completely transformed the AFE phase into the FE phase by depinning the pinned domains. The influence of field cycling on the interfacial layer was also examined through the pulse-switching experiments.